Evaluation of serum anti-nuclear antibodies and anti-dsDNA in patients with systemic lupus erythematosus - Nguyen, Thi Huyen; Leonardo, Antonio Sechi; Le, Van Chi; Nguyen, Vu Thanh; Phan, Thi Minh Phuong (Tạp chí Y Dược Huế, 2024)
Background: Systemic lupus erythematosus (SLE) is characterized by the production of autoantibodies and dysregulation of cytokines. This study aimed to describe the results of anti-nuclear antibodies (ANA) and antibodies against double-stranded DNA (anti-dsDNA) tests in patients with SLE and to investigate the association between anti-dsDNA and ANA. Materials and methods: A retrospective data and cross-sectional descriptive study were conducted on 147 patients diagnosed with SLE who attended Hue University of Medicine and Pharmacy Hospital from January 2018 to April 2023. Results: The mean age of the study population was 32.2 ± 13.6 years, with the most common age range being 20 to below 40 years (59.2%). The prevalence of SLE in females was observed in 127 out of 147 (86.4%) patients, which was 6.35 times higher than in males. The rates of ANA and anti-dsDNA positivity in SLE patients were 57.1% and 29.9%, respectively. The prevalence of positive ANA result tests in females was higher than in males, with a statistically significant difference (p<0.05). Specifically, the rate of positive anti-dsDNA in ANA-positive patients (52.4%) was significantly higher compared to ANA-negative patients (0.0%) (p<0.05). Conclusions: The prevalences of positive ANA and anti-dsDNA test results in patients with SLE were 57.1% and 29.9%, respectively. There is a statistically significant association between anti-dsDNA and ANA test results in patients with SLE (p<0.05).